2022
DOI: 10.1001/jamaophthalmol.2022.4394
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Incidence of Dry Eye and Meibomian Gland Dysfunction in the United States

Abstract: ImportanceDry eye is a common clinical manifestation, a leading cause of eye clinic visits, and a significant societal and personal economic burden in the United States. Meibomian gland dysfunction (MGD) is a major cause of evaporative dry eye.ObjectiveTo conduct a systematic review and meta-analysis to obtain updated estimates of the prevalence and incidence of dry eye and MGD in the United States.Data SourcesOvid MEDLINE and Embase.Study SelectionA search conducted on August 16, 2021, identified studies publ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(28 citation statements)
references
References 55 publications
(173 reference statements)
0
20
0
Order By: Relevance
“…The lack of a consistent seasonal variation in DED could be related to a geographical impact. In the US, the prevalence of DED appeared higher in the southern regions 16 . In our study, all patients were examined at a single location.…”
Section: Discussionmentioning
confidence: 92%
“…The lack of a consistent seasonal variation in DED could be related to a geographical impact. In the US, the prevalence of DED appeared higher in the southern regions 16 . In our study, all patients were examined at a single location.…”
Section: Discussionmentioning
confidence: 92%
“…Second, the socioeconomic status definition used in the current study focuses on two of the five key domains of social determinants of health (economic stability and education). Studies have shown that dry eye disease–related outcomes may be impacted by the three other domains as well: health care access and quality (e.g., we did not ask about whether the respondent had regular access to an eye care provider), 28,29 neighborhood and built environment (e.g., we did not ask about the respondent's occupation, such as whether they worked indoors or outdoors), 14,15,22,30–34 and social and community context (e.g., we did not ask about the respondent's residential geographical region and weather-related context in the United States) 29,35,36 . Third, we did not ask whether the respondent's dry eye symptoms may have been related to individual factors, such as contact lens use and underlying health conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Dry eye disease is prevalent in the United States. Our systematic review and meta-analysis of recent (2010 to 2021) studies found the overall prevalence in the United States to be 8.1% (95% confidence interval, 4.9 to 13.1%) 5 . Dry eye disease–related symptoms, such as dryness and visual difficulty, are among the leading concerns that make patients seek eye care.…”
mentioning
confidence: 88%
“…Dry eye is a multifactorial age-related ocular surface disease with a high prevalence of disease in the world, ranging from 5 to 50% [ 1 , 2 , 3 ]. Dry eye is characterized by the instability of tear film on the ocular surface, leading to the various symptoms that influence the productivity at the workplace due to the lower quality of vision [ 4 ].…”
Section: Introductionmentioning
confidence: 99%